2020
DOI: 10.1002/adfm.201909614
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fluorescence for Bioassembly by Environment‐Switching Doping of Metal Ions

Abstract: The self‐assembly of cyclodipeptides composed of natural aromatic amino acids into supramolecular structures of diverse morphologies with intrinsic emissions in the visible light region is demonstrated. The assembly process can be halted at the initial oligomerization by coordination with zinc ions, with the most prominent effect observed for cyclo‐dihistidine (cyclo‐HH). This process is mediated by attracting and pulling of the metal ions from the solvent into the peptide environment, rather than by direct in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…[10h, 17] MD simulations can be powerful tools in providing insights into molecular self-assembly by analyzing the initial nucleation of molecules in different environments. [18] Here,w eperformed multiple multi-ns explicit solvent MD simulations in CHARMM [19] to investigate the initial stages of cyclo-HH self-assembly in the presence of Zn 2+ and iodide ions.Across all simulations,visual inspection confirmed that disordered aggregates of cyclo-HHmolecules were reformed, indicating that the cyclo-HHmolecules were not trapped in al ocal energetic minimum in ag iven simulation and facilitated higher-order structures.W ithin the simulations,o rdered antiparallel and parallel configurations of cyclo-HH dimers were observed, with the former being the predominant configuration (Figure S9, Table S1), in line with the crystallographic data (Table S2). According to the time-evolution structural analysis of the antiparallel configurations (Figure S9, Table S1), the elementary unit Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…[10h, 17] MD simulations can be powerful tools in providing insights into molecular self-assembly by analyzing the initial nucleation of molecules in different environments. [18] Here,w eperformed multiple multi-ns explicit solvent MD simulations in CHARMM [19] to investigate the initial stages of cyclo-HH self-assembly in the presence of Zn 2+ and iodide ions.Across all simulations,visual inspection confirmed that disordered aggregates of cyclo-HHmolecules were reformed, indicating that the cyclo-HHmolecules were not trapped in al ocal energetic minimum in ag iven simulation and facilitated higher-order structures.W ithin the simulations,o rdered antiparallel and parallel configurations of cyclo-HH dimers were observed, with the former being the predominant configuration (Figure S9, Table S1), in line with the crystallographic data (Table S2). According to the time-evolution structural analysis of the antiparallel configurations (Figure S9, Table S1), the elementary unit Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Fmoc-3,4F-Phe and Fmoc-3,5F-Phe were computationally modeled independently for use as initial structures in MD simulations, described in the next section, analogously to refs [52,53]. For each system, 36 monomers (either Fmoc-3,4F-Phe or Fmoc-3,5F-Phe) were embedded in a 40 × 40 × 60 Å 3 grid within a 90 × 90 × 90 Å 3 water box, with an equal spacing of approximately 20 Å between each monomer and random configurations and orientations.…”
Section: Molecular Modeling Of Investigated Systemsmentioning
confidence: 99%
“…The random configurations were extracted from short simulations of each monomer at infinite dilution. The derivative concentration within each system was higher than the concentration used in the experimental studies, aiming to artificially accelerate the self-assembly within the frame of the simulations [52,53].…”
Section: Molecular Modeling Of Investigated Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another's investigated the effect of metal ions on zeta potential [24] and the evolution of the structural and electrical properties of containing for the metal ion [25]. At the moment, some research dope the metal ions with some chemical compounds and study the influence on some physical properties [26,27]. But most research absences a theoretical work that summarizes the behavior of the metal ions spectra to be a reference.…”
Section: Introductionmentioning
confidence: 99%